2020
DOI: 10.1101/2020.08.24.20181289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal Fluid Lactate as a Prognostic Marker of Disease Severity and Mortality in Cryptococcal Meningitis

Abstract: Background: Cerebrospinal fluid (CSF) lactate levels can differentiate between bacterial and viral meningitis. We measured CSF lactate in individuals with cryptococcal meningitis to determine its clinical significance. Methods: We measured point-of-care CSF lactate at the bedside of 319 HIV-infected Ugandan adults at diagnosis of cryptococcal meningitis. We summarized demographic variables and clinical characteristics by CSF lactate tertiles. We evaluated the association of CSF lactate with clinical characte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…A superior approach is to combine these two diagnostic methods. We found that seizure and altered consciousness are associated with an increased risk of 1-year death in CM, which is consistent with previous findings (19,20). Moreover, we observed that the number of symptoms shows positive correlation with the risk of death.…”
Section: Discussionsupporting
confidence: 92%
“…A superior approach is to combine these two diagnostic methods. We found that seizure and altered consciousness are associated with an increased risk of 1-year death in CM, which is consistent with previous findings (19,20). Moreover, we observed that the number of symptoms shows positive correlation with the risk of death.…”
Section: Discussionsupporting
confidence: 92%